Overview of Healthcare-Related Infections in Intensive Care Units of a public hospital - Garcez, Marília Victória Nunes Garcez; Campelo, Sônia Maria de Araújo; Ribeiro, Ivonizete Pires; Barros, Gabriel Martins de Barros; Silva, Anneth Cardoso Basílio da; Costa, Francimar Lima da; Lima, Andréa Conceição Gomes; Avelino, Fernanda Valeria Silva Dantas (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Healthcare-Associated Infections are illnesses acquired after the patient's admission to the hospital unit and which manifest themselves during hospitalization or after discharge. Aim: To analyze the panorama of health-related infections in patients admitted to intensive care units. Outlining: Cross-sectional, retrospective study, collected from the Hospital Infection Control Commission database in a public hospital from July to December 2022. Crude and adjusted odds ratios were calculated using logistic regressions. The study followed the ethical and legal precepts of resolution 466/2012. Results: There was a predominance of males and those aged over 60 years. The main clinical problems were co infection with COVID-19 and co-infection with HIV. Regarding previous conditions, Systemic Arterial Hypertension stood out. When analyzing the etiological agents, the presence of Klebsiella pneumoniae showed a marginally significant association with an increase in the chances of death. Implications: The use of invasive devices, prolonged hospital stay and other factors such as age, associated comorbidities, were predictors of mortality among patients, as well as risk factors for the development of Klebsiella Pneumoniae Carbapenemase infection.